2018
DOI: 10.1007/s11869-018-0567-3
|View full text |Cite
|
Sign up to set email alerts
|

Concern over health effects of air pollution is associated to NO2 in seven European cities

Abstract: Subjective perception of air pollution is important, and can have impacts on health in its own rights, lead to protective behaviour, or it can be leveraged to engage citizens and stakeholders in support of cleaner air policies. The aim of the current analysis was to examine associations between level of concern over health effects of air pollution and personal and environmental factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 39 publications
5
26
0
Order By: Relevance
“…Three articles are multicenter studies, two are surveys performed in seven countries [ 35 , 54 ], and the remaining are surveys performed in six countries [ 74 ]. Six studies were based on a national-level [ 41 , 47 , 49 , 52 , 60 , 67 ], three on multi-province [ 40 , 45 , 57 ], and seven on multiple-city surveys [ 50 , 51 , 59 , 63 , 64 , 71 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three articles are multicenter studies, two are surveys performed in seven countries [ 35 , 54 ], and the remaining are surveys performed in six countries [ 74 ]. Six studies were based on a national-level [ 41 , 47 , 49 , 52 , 60 , 67 ], three on multi-province [ 40 , 45 , 57 ], and seven on multiple-city surveys [ 50 , 51 , 59 , 63 , 64 , 71 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…As for the procedures of the studies included in the systematic review, field studies [ 50 , 58 , 69 , 72 ], telephone survey studies [ 42 , 48 , 68 , 70 , 71 , 73 ], on-line surveys [ 44 , 54 , 57 , 61 ], and mixed procedure studies [ 53 ] were found. In the context of field studies, face-to-face interviews were the fundamental, but sometimes not unique, method employed to collect the data of interest to be related to the objective levels of pollution [ 34 , 42 , 50 , 55 , 58 , 59 , 60 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in accordance with the association observed between urban density and NO2 levels and more walking because exposure to air pollution (and therefore annoyance by it) is more intense in dense urban areas. In fact, in a previous PASTA study, researchers already observed that increasing NO2 levels at the home address was associated with concerns over the health effects of air pollution (Dons et al. 2018).…”
Section: Discussionmentioning
confidence: 99%
“…China's economy has made remarkable achievements over the past 40 years, but it leads to the huge damage to natural resources and environment. Water pollution, soil pollution, and other environmental issue have exploded in recent years, which have posed a great threat to the health of residents [1][2][3][4]. Particularly, air pollution has been more serious beyond expectation and the haze is the mostly attributed causes for pneumonia.…”
Section: Introductionmentioning
confidence: 99%